Detection of Mycoplasma hyopneumoniae by Air Sampling with a Nested PCR Assay - Stärk, Katharina D. C. (American Society for Microbiology, 1998)
This article describes the first successful detection of airborne Mycoplasma hyopneumoniae under experimental and field conditions with a new nested PCR assay. Air was sampled with polyethersulfone membranes (pore size, 0.2 μm) mounted in filter holders. Filters were processed by dissolution and direct extraction of DNA for PCR analysis. For the PCR, two nested pairs of oligonucleotide primers were designed by using an M. hyopneumoniae-specific DNA sequence of a repeated gene segment. A nested PCR assay was developed and used to analyze samples collected in eight pig houses where respiratory problems had been common. Air was also sampled from a mycoplasma-free herd. The nested PCR was highly specific and 10(4) times as sensitive as a one-step PCR. Under field conditions, the sampling system was able to detect airborne M. hyopneumoniae on 80% of farms where acute respiratory disease was present. No airborne M. hyopneumoniae was detected on infected farms without acute cases. The chance of successful detection was increased if air was sampled at several locations within a room and at a lower air humidity.